2020
DOI: 10.1002/lno.11593
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of a blooming jellyfish (Aurelia coerulea) in a Mediterranean coastal lagoon

Abstract: The current lack of knowledge on the trophic ecology of scyphozoans, particularly at the benthic stage, prevents a full understanding of the controls on many jellyfish blooms. The blooming scyphozoan (Aurelia coerulea) completes its entire life cycle in the Thau lagoon (southern France), where the annual population dynamics of both its benthic and pelagic stages have been described. This offered an exceptional framework to investigate the trophic processes regulating jellyfish populations over time. To this ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(153 reference statements)
1
6
0
Order By: Relevance
“…Additionally, A. labiata collected in the current study in September spanned the size range of 25-225 mm, so variability in trophic levels and resource competition likely also exists at any given time. Size-based diet shifts have also been documented for other species of jellyfish (used here to mean medusozoans; Graham & Kroutil, 2001;Marques et al, 2021;Nagata & Morandini, 2018;Sullivan et al, 1994). A positive relationship between bell diameter and δ 15 N is commonly seen in jellyfish (Fleming et al, 2015;Malej et al, 1993;Nagata et al, 2015), and qualitative assessments have indicated a shift in prey from seston to zooplankton (Wang et al, 2020;Ying et al, 2012), similar to what was found here.…”
Section: Diet Shifts In a Labiatasupporting
confidence: 77%
“…Additionally, A. labiata collected in the current study in September spanned the size range of 25-225 mm, so variability in trophic levels and resource competition likely also exists at any given time. Size-based diet shifts have also been documented for other species of jellyfish (used here to mean medusozoans; Graham & Kroutil, 2001;Marques et al, 2021;Nagata & Morandini, 2018;Sullivan et al, 1994). A positive relationship between bell diameter and δ 15 N is commonly seen in jellyfish (Fleming et al, 2015;Malej et al, 1993;Nagata et al, 2015), and qualitative assessments have indicated a shift in prey from seston to zooplankton (Wang et al, 2020;Ying et al, 2012), similar to what was found here.…”
Section: Diet Shifts In a Labiatasupporting
confidence: 77%
“…Aurelia spp. are known to be able to thrive on very small zooplankton 75 and indeed feeding experiments on Aurelia aurita from the Black Sea suggest that food items overlooked by researchers appraising prey visually may provide ten times the energy for Aurelia than that obtained from mesozooplankton 76 : it is possible that Aurelia medusa could be sustained by cyphonautes. Another possibility is that environmental conditions that favour strobilation (asexual reproduction) of Aurelia benthic phases also favour bryozoan reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the intraguild predation of C. nozakii that N. nomurai and small medusae were the main prey items of this species (Wang et al, 2020), and N. nomurai was found to have higher δ 13 C and δ 15 N values (-16.80 ± 1.28 and 8.11 ± 1.45 , respectively) than R. esculentum in our study (as discussed below). On the other hand, the differences in the sampling year might also lead to different δ 13 C and δ 15 N values between R. esculentum and C. nozakii since temporal variations of δ 13 C and δ 15 N values have been reported in several previous studies performed on jellyfish (Fleming et al, 2015;Javidpour et al, 2016;Marques et al, 2020). Significant spatial variations were found in δ 13 C and δ 15 N values among origins (ANOVA, δ 13 C: F 2,65 = 66.66, p < 0.01; δ 15 N: F 2,65 = 255.17, p < 0.01, Figure 2).…”
Section: Rhopilema Esculentum and Implications For Origin Traceabilitymentioning
confidence: 99%